Effect of emulsifying stability of myofibrillar protein on the gel properties of emulsified surimi gel - Gao, Yuanpei (Food Sci Nutr, 2018)
Several kinds of emulsified surimi gels were prepared from different quality levels of Alaska Pollack surimi, and the relationship between the emulsifying stability (ES) of myofibrillar protein and the properties of the emulsified surimi gels was investigated. Fish oil emulsified into surimi gels enhanced the breaking strength, but this was decreased by denaturation of the surimi protein, and the rate of enhanced gel‐forming ability with emulsification decreased with decreasing ES. Expressible drip also decreased with emulsification; however, increasing amounts of lipid in the expressible drip were separated out from the gel upon protein denaturation of the source surimi. Scanning electron microscopy revealed that the shape of fish oil particles became irregular and some voids caused by oil leakage were observed with increasing storage period of source surimi. The results suggested that improvement in gel properties of the emulsified surimi gels was correlated with ES as well as the level of protein denaturation.